IDIOMS IN ENGLISH ON TOPIC OF THE HEALTH : THEIR LITERAL AND REAL MEANINGS , TRANSLATIONS AND USE IN CONTEXT - Alaydinova Maharramxon Islombek qizi (PEDAGOGS, 2025)
Annotation: This article focuses on the study of English idioms related to the topic of health. It provides the definition and classification of idioms, explains their figurative meanings, and analyzes their Uzbek translations. The paper also demonstrates how health-related idioms are used in real contexts. The study aims to highlight the importance of understanding idioms for effective communication and translation. The results can be useful for English language learners, teachers, and translators.